Can Restoration of Freshwater Mineral Soil Wetlands Deliver Nature-Based Climate Solutions to Agricultural Landscapes? - Creed, Irena F.; Badiou, Pascal; Enanga, Eric; Lobb, David A.; Pattison-Williams, John K.; Lloyd-Smith, Patrick; Gloutney, Mark (Frontiers in Ecology and Evolution, 2022)
This study advances scientific understanding of the magnitude of carbon sequestration that could be achieved through conservation (securing existing carbon stocks) and restoration (creating new carbon stocks) of freshwater mineral soil wetlands on agricultural landscapes. Within an agricultural landscape in southern Ontario (Canada), 65,261 wetlands comprising 63,135 ha were lost. Of these, 6,899 wetlands comprising 5,198 ha were “easy-to-restore” wetlands, defined as wetlands that were small (<0.5 ha), with no hydrological inflow or outflow, and that were drained by a ditch and could be restored by plugging the ditch. Within these easy-to-restore wetlands, a chronosequence that covered a range of restoration ages (i.e., drained (0 years), 15 years, 25 years, 40 years, and intact marshes) was established to capture potential changes in rates of sedimentation and organic carbon (OC) sequestration. Three sediment cores were collected at the centre of the open-water portion of the wetland and segmented in the field. In the lab, each individual segment from each core was dried, sieved through a 2-mm mesh, weighed and analyzed for 137Cs and 210Pb radioisotopes and OC. OC stocks (35.60 Mg ha-1) and OC sequestration rates (0.89 Mg C ha-2 yr-1) in wetlands restored for 40 years were comparable to if not marginally larger than intact wetlands. An economic analysis to compare the costs and benefits of wetland conservation and restoration was then conducted. The benefit-cost analysis revealed that the financial benefits of carbon sequestration are greater than the financial costs over a 30-year time horizon for retaining wetlands but not for restoring wetlands. The breakeven costs such that wetland restoration is economically feasible based on current carbon price projections is estimated to be 17,173 CAD ha-1 over the 30-year time horizon; any wetland restoration project that costs this amount or less could be justified on economic grounds based solely on the carbon benefits. This study’s findings indicate that wetlands are important NbCS, but that incentivizing their use through a carbon market will require either scientific innovations to reduce restoration costs or increase carbon sequestration rates, or stacking carbon benefits with other ecosystem service benefits into a comprehensive market for NbCs.